Bromelain-Extracted of Virgin Coconut Oil: Physical and Chemical Stability in Different Temperature During the Storage - Harimurti, Sabtanti; Sukamdi, Dyani Primasari; Widada, Hari; Sari, Hasna Fadia; Amid, Azura (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The bromelain-enzymatic reaction is applied in virgin coconut oil (VCO) production. Hydrolysis of the emulator by bromelain enzyme in coconut milk during fermentation maximized further the separation of oil and water. In the higher demand for VCO in many industries, the VCO stability during transportation and storage must be evaluated. The research aims to evaluate the physical and chemical stability of the effect of temperature in the storage. VCO's physical and chemical stability was evaluated under two different temperature and storage periods: an elevated temperature of 50°C for 10 days and room temperature (27-30°C) for 50 days. The storage was conducted in a clear glass bottle. The evaluation was based on physical and chemical stability tests before and after storage, including organoleptic, pH changes, density, viscosity, acid number, peroxide number, and saponification number. Based on the data, the quality of the VCO after storing at 50°C for 10 days and 27-30°C for 50 days was found to be changed for pH, specific gravity, viscosity, acid number, peroxide number, saponification number, while for the appearance was found to be no changes. The VCO was very sensitive to environmental effects. Therefore, it is necessary to find the best storage chamber and temperature for stabilizing the VCO.